Monitoring urban land cover with the use of satellite remote sensing techniques as a means of flood risk assessment in Cyprus - Agapiou, Athos; Themistocleous, Kyriacos; Hadjimitsis, Diofantos G.; Alexakis, Dimitrios (My University, 2011)
The increase of flood inundations occurring in different regions all over the world has enhanced the need for effective flood risk management. A flood can be determined as a mass of water that produces runoff on land that is not normally covered by water. This study strives to highlight the need of digital mapping of urban sprawl in a catchment area in Cyprus and the assessment of its contribution to flood risk. The Yialias River (Nicosia, Cyprus) was selected as case study where devastating flash floods events took place at 2003 and 2009. In order to search the diachronic land cover regime of the study area multi-temporal satellite imagery was processed and analyzed, (ASTER). A classification model is proposed based on spectral, texture and shape features in order to create efficient land use and land cover maps. GIS were used to detect identifying trends, both visually and statistically, resulting from land use changes in a flood prone area such as Yialias by the use of spatial metrics. The results indicated that there is a considerable increase of urban areas cover during the last 10 years. All these denoted that one the main driving force of the increasing flood risk in catchment areas in Cyprus is generally associated to human activities
Keywords: Classification; Land cover; Landscape metrics; Satellite imagery; Texture